Relationships between power and strength of the upper and lower limb muscles and throwing velocity in male handball players - Chelly, M. S.; Hermassi, S.; Shephard, R. (The Journal of Strength and Conditioning Research, 2010)
This study aimed to investigate relationships between peak power (PP) as measured by upper limb (PPUL) and lower limb (PPLL) force-velocity tests, maximal upper limb force assessed by 1 repetition maximum bench press (1RMBP), and pullover (1RMPO) exercises, estimates of local muscle volume and 3-step running handball throwing velocity (T3-Steps). Fourteen male handball players volunteered for the investigation (age: 19.6 ± 0.6 years; body mass: 86.7 ± 12.9 kg; and height 1.87 ± 0.07 m). Lower and upper limb force-velocity tests were performed on appropriately modified forms of a Monark cycle ergometer, with measurement of PPUL and PPLL, and the corresponding respective maximal forces (F0UL and F0LL) and velocities (V0UL and V0LL). T3-Steps was assessed using a radar Stalker ATS system™. Muscle volumes of the upper and lower limbs were estimated with a standard anthropometric kit. T3-Steps was closely related to absolute PPUL and to F0UL (r = 0.69, p < 0.01 for both relationships). T3-Steps was also moderately related to 1RMBP and 1RMPO (r = 0.56, p < 0.05; r = 0.55, p < 0.05 respectively), and to PPLL and F0LL (r = 0.56, p < 0.05; r = 0.62, p < 0.05, respectively). When PPLL was expressed per unit of limb muscle volume, the relationship with T3-Steps disappeared. This suggests the importance of muscle volume to performance in throwing events. Force-velocity data may prove useful in regulating conditioning and rehabilitation programs for handball players. Our results also highlight the contribution of both the lower and the upper limbs to handball throwing velocity, suggesting the need for coaches to include upper and lower limb strength and power programs when improving the throwing velocity of handball players.